Funções afim e quadrática com auxílio do multiplano e blocos cúbicos - Silva, João Paulo Arruda da (2014)
This paper presents a new way of discussing concepts involving function, a ne function and quadratic function. Through simple activities with the use of blocks of cubes, and the multiplane software such as GeoGebra, students will move from a passive position, as simple listener, the active member of the teaching-learning process, enabling them to acquire a broader notion the concept of function and apply it later in solving problems in school and in their daily lives. Besides these diversi ed activities, topics that are usually not given prominence in most books of high school such that the analysis of the canonical form of the quadratic function and the theorem of characterization of a ne function will play an important role in developing what is expected of students about this important area of mathematics. All activities were conducted with 1st grade students of high school Natalicia Maria Figueiroa da Silva, located in the city of Surubim, in the state of Pernambuco.